Template-free synthesis of carbon doped TiO2 mesoporous microplates for enhanced visible light photodegradation - Liu, Jian; Han, L.; Ma, H.; Tian, H.; Yang, J.; Zhang, Q.; Seligmann, Ben; Wang, Shaobin; Liu, J. (Science in China Press, 2016)
© 2016 Science China Press and Springer-Verlag Berlin Heidelberg. Titanium dioxide (TiO2) is widely employed as a solid photocatalyst for solar energy conversion and environmental remediation. The ability to construct porous TiO2 with controlled particle size and narrowed bandgap is an essential requirement for the design of highly efficient and recyclable photocatalysts. Here, we report a template-free acetic acid induced method for the synthesis of visible-light responsive carbon-doped TiO2 microplates with high crystallinity and mesoporous structure. It is shown that the electron-withdrawing bidentate carboxylate ligands derived from acetic acid can narrow the bandgap of TiO2 (1.84 eV) substantially. Moreover, the resultant microplate photocatalysts exhibit excellent photocatalytic efficiency and solid–liquid separation performance, which will be beneficial for future industrial applications.